SHOULD HIGHER EDUCATION MEET THE DEMAND IN THE LABOR MARKET? - Alexandra A. Moskovskaya (Высшее образование в России)
The article is devoted to the imaginary and the real challenges facing universities in connection with the problem of matching between skills of graduates and skills demanded by employers. It shows that the labor market demand is indirect, not a direct reference point for universities, and can best be satisfied if a University in its goals and curriculums is ahead of the demand in the economy and not follows it.